Sustained Inhibition of Proliferative Response After Transient FGF Stimulation Is Mediated by Interleukin 1 Signaling. Issue 3 (March 2016) - Poole, Ashleigh; Kacer, Doreen; Cooper, Emily; Tarantini, Francesca; Prudovsky, Igor
Abstract : Transient FGF stimulation of various cell types results in FGF memory—a sustained blockage of efficient proliferative response to FGF and other growth factors. FGF memory establishment requires HDAC activity, indicating its epigenetic character. FGF treatment stimulates proinflammatory NFκB signaling, which is also critical for FGF memory formation. The search for FGF‐induced mediators of FGF memory revealed that FGF stimulates HDAC‐dependent expression of the inflammatory cytokine IL1α. Similarly to FGF, transient cell treatment with recombinant IL1α inhibits the proliferative response to further FGF and EGF stimulation, but does not prevent FGF receptor‐mediated signaling. Interestingly, like cells pretreated with FGF1, cells pretreated with IL1α exhibit enhanced restructuring of actin cytoskeleton and increased migration in response to FGF stimulation. IRAP, a specific inhibitor of IL 1 receptor, and a neutralizing anti‐IL1α antibody prevent the formation of FGF memory and rescue an efficient proliferative response to FGF restimulation. A similar effect results following treatment with the anti‐inflammatory agents aspirin and dexamethasone. Thus, FGF memory is mediated by proinflammatory IL1 signaling. It may play a role in the limitation of proliferative response to tissue damage and prevention of wound‐induced hyperplasia. J. Cell. Physiol. 231: 650–658, 2016. © 2015 Wiley Periodicals, Inc.